Comparative visibility of four spoken languages - Oyer HJ; Richard R; Rajaguru R; Kapur YP`` (Journal of All India Institute of Speech and Hearing, 1972)
Casual observation of persons speaking different languages reveals that somelanguages are more highly visible than others. This observation is not only ofacademic interest to the linguist but also of interest to the rehabilitative audiologistwho wishes to add to his store of information concerning the effects of "code" uponthe lipreadability of certain languages. The authors are quite cognizant of the fact,however, that there is variability within languages vis-a-vis visibility, as a function ofindividual speaker differences, and also as a function of the language units spoken.Through the use of an appropriate experimental design and careful administration ofan experiment, it is possible to obtain data concerning visibility of languages thatlend themselves to treatment which provide a base for making reasoned generalizationsabout the relative visibility of languages.